Analysis and design of different controllers for non-linear power systems - Chaudhary, Rekha; Singh, Arun Kumar (International Journal of Engineering and Technology, 2013)
The objective of this paper is to design controller for non-linear power system using Direct Feedback Linearization technique to improve the transient stability and to achieve better voltage regulation. In case of fault in the power system, power angle and the terminal voltage are the parameters which are to be monitored. The simulation has been carried out taking different values of initial power angles and results were obtained for power angle and terminal voltage. To overcome the demerits of DFL-LQ optimal controller and DFL voltage regulator, co-ordinated controller is proposed. Simulation results show that transient stability of a power system under a large sudden fault has been improved by using co-ordinated controller.